Allometric models for estimating aboveground biomass and carbon stocks of the semi-arid savanna woody species, Detarium microcarpum Guill. et Perr. - Adama Taonda; Issouf Zerbo; Innocent Charles Emmanuel Traore; Fousseni Folega; Anny Estelle N'Guessan; Justin N'Dja Kassi; Adjima Thiombiano (Scientific African)
Quantification of plant biomass and carbon is critical for the savanna species. The lack of accurate biomass tools is a challenge for the savanna species. Information on allometric equations is limited for Detarium microcarpum species. This study aimed to develop an allometric equation for the aboveground biomass of D. microcarpum across the two climatic zones. A total of 60 trees were considered using the destructive method. Three equations were tested with a diameter at the breast (dbh) alone, height (ht) as additional (dbh*ht), and diameter in combination with height (dbh2*ht) as predictors using log-transformed data with a power function. Their performance was assessed with the adjusted R-square (Adj.R2), Akaike Information Criteria (AIC), correction factors (CF), and the Root Mean Square Error (RMSE). The performance of the validated allometric models was compared with the generalized pantropical equation (Chave et al., 2014). The results revealed that the diameter is a good predictor in the Sudano-Sahelian zone and for branches and leaves biomass estimates in the Sudanian zone. The stem requires ht with the dbh (dbh2*ht) in the Sudano-Sahelian zone.The allometric models established to predict D. microcarpum biomass wereTAGB = e4.4002 (dbh*dbh*h) 0.9456 + e-3.5219 (dbh)2.4007 + e-2.8845(dbh)1.3465 in the Sudanian zone and TAGB = e-4.1053 (dbh)2.4222 + e-5.2567(dbh)2.9539 + e-2.9894(dbh)1.5285 for the Sudano-Sahelian climatic zone. The equations developed in this study are useful tools for assessing the aboveground biomass and the carbon of the savanna multipurpose species.